Encyclopedia of food microbiology - Voet, Donald (John Wiley & Sons, 2004)
The content of this book is organized into five parts: Introduction and Bacground; Biomolecules; Mechanisms of Enzymen Action, Metabolism; and Expression and Transmission of Genetic Information. This organization permits us to cover the major areas of biochemistry in a logical and coherent fashion.